On the syntax of possessor raising in Swahili - Camillia N. Keach (LibraryPress@UF, 1992)
Traditionally Possessor Raising (PR) in Swahili is included with a variety of sentence types as an instance of the Nominal Construction and more recently defended as a member of that class. This study has two major goals: fIrst, it demonstrates that PR has syntactic distributional patterns which argue against its inclusion in the Nominal Construction. Secondly, it addresses a central question: what features of an explicit grammar explain the syntactic properties associated with PR? After showing that the inferentially based proposals in Hinnebusch and Kirsner [1980] and in Scotton [1981] do not adequately characterize PR nor accommodate its syntax, semantics or interpretation, we present a Government Binding treatment ofPR's syntax. Finally, we provide a summary of our cross-linguistic research on PR's interpretation.